The integration of health equity into policy to reduce disparities: Lessons from California during the COVID-19 pandemic. - Ada T Kwan; Jason Vargo; Caroline Kurtz; Mayuri Panditrao; Christopher M Hoover; Tomás M León; David Rocha; William Wheeler; Seema Jain; Erica S Pan; Priya B Shete (PLoS ONE, 2025)
Racial and ethnic minoritized groups and socioeconomically disadvantaged communities experience longstanding health-related disparities in the United States and were disproportionately affected throughout the COVID-19 pandemic. How departments of public health can explicitly address these disparities and their underlying determinants remains less understood. To inform future public health responses, this paper details how California strategically placed health equity at the core of its COVID-19 reopening and response policy, known as the Blueprint for a Safer Economy. In effect from August 2020 to June 2021, "the Blueprint" employed the use of the California Healthy Places Index (HPI), a place-based summary measure of 25 determinants of health constructed at the census tract level, to guide activities. Using California's approach, we categorized the state population by HPI quartiles at the state and within-county levels (HPIQ1 representing the least advantaged, HPIQ4, the most advantaged) from HPI data available to demonstrate how the state monitored crude COVID-19 test, case, mortality, and vaccine rates and unadjusted rate ratios (RR) using equity metrics developed for the Blueprint. Notable patterns emerged. Testing disparities disappeared during the summer and winter surges but resurfaced between surges. Monthly case RR peaked in May 2020 for HPIQ1 compared to HPIQ4 (RR 6.61, 95%CI: 6.41-6.81), followed by mortality RR peaking in June 2020 (RR 5.06, 95% CI: 4.34-5.91). As the pandemic wore on, disparities in unadjusted case and mortality RRs between lower HPI quartiles relative to HPIQ4 reduced but remained. Utilizing a place-based index, such as HPI, enabled a data-driven approach that used a determinants of health lens to identify priority communities, allocate resources, and monitor outcomes based on need during a large-scale public health emergency.